Pengaruh Sensitivitas Industri, Umur Perusahaan, dan Kinerja Lingkungan terhadap Pengungkapan Informasi Lingkungan (Studi Empiris padaPerusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Pratiwi Wirmaningsih; Mia Angelina Setiawan (Universitas Negeri Padang, 2022)
This study aims to see the effect of industrial sensitivity, firm age, and environmental performance on environmental information disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX), the research sample was determined using the purposive sampling method with a total sample of 48 companies. The data used is secondary data from the company’s annual report. The analytical method used is multiple linear regression analysis. The results showed that industrial sensitivity does not significant effect on environmental information disclosure. Firm age and environmental performance has significant effect on environmental information disclosure.